Теоретичні засади антропоніміки як галузі мовознавства - Лісова, Лариса Олександрівна; Lisova, Larysa O. (Східноєвропейський національний університет, 2013)
У статті проаналізовано основні напрями дослідження українських прізвищ, погляди учених-ономастів на історію формування та сучасний стан антропонімії. Окреслено здобутки вчених в опрацюванні давніх і сучасних українських прізвищ. Теоретичний аналіз праць з антропоніміки дозволив виділити низку лінгвістичних проблем та різні підходи вчених у лінгвістичній науці. Main directions of study of the Ukrainian last names are analysed in the article, looks of scientists on history of forming and modern state of anthroponomastics. Achievements of scientists are analysed in the study of the Ukrainian last names. The theoretical analysis of labours from anthroponomastics allowed to select the row of linguistic problem and different approaches of scientists in linguistic science. Scientific labours from Ukrainian anthroponym appear from the second half of ХХ century, when the study of the last names was carried out mainly in ethnographic and in a civilized manner-social aspects. From the second half of ХХ century of the last name begin to examine in etymologic, word-formation plans, labours, devoted the study of Ukrainian historical anthroponym, appear. At the end of ХХ century – at the beginning XXI century activate regional researches of Ukrainian anthroponym, the lexicographic analysis of the last names of separate territories begins.
Theoretical Principles of Anthroponomastics as Industries of Linguistics
Keywords: прізвище; антропоніміка; антропонім; ономастика; онім; family name; anthroponomastics; anthroponym; onomastics; onim